Analisis efektivitas pengelolaan dana alokasi khusus bantuan operasional penyelenggaraan pendidikan anak usia dini (BOP-PAUD): Studi Kasus Pada TK Kemala Bhayangkari 62 Boyolali - Arum, Anita Ambar (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This study aims to analyze the management of the Special Allocation Fund for Operational Assistance in Early Childhood Education (BOP-PAUD) at TK Kemala Bhayangkari 62 Boyolali, focusing on its compliance with the principles of BOP fund utilization and the effectiveness of its management during the 2021–2023 period. The research is grounded in the importance of transparent, accountable, and well-targeted educational funding to enhance the quality of early childhood education services. A descriptive quantitative approach was employed, with data analysis encompassing data reduction, data presentation, conclusion drawing, and effectiveness assessment based on predetermined indicators. The findings reveal that the management of BOP-PAUD at TK Kemala Bhayangkari 62 Boyolali adheres to the implementation principles, including planning, execution, bookkeeping, reporting, and accountability. The management effectiveness during 2021–2023 is classified as high, although challenges remain, such as delays in fund disbursement and limited supporting resources.